Modulation of Intestinal ILC3 for the Treatment of Type 1 Diabetes - Stojanović, Ivana; Saksida, Tamara; Miljković, Đorđe; Pejnović, Nada (Frontiers in Immunology, 2021)
Gut-associated lymphoid tissue (GALT) is crucial for the maintenance of the intestinal homeostasis, but it is also the potential site of the activation of autoreactive cells and initiation/propagation of autoimmune diseases in the gut and in the distant organs. Type 3 innate lymphoid cells (ILC3) residing in the GALT integrate signals from food ingredients and gut microbiota metabolites in order to control local immunoreactivity. Notably, ILC3 secrete IL-17 and GM-CSF that activate immune cells in combating potentially pathogenic microorganisms. ILC3 also produce IL-22 that potentiates the strength and integrity of epithelial tight junctions, production of mucus and antimicrobial peptides thus enabling the proper function of the intestinal barrier. The newly discovered function of small intestine ILC3 is the secretion of IL-2 and the promotion of regulatory T cell (Treg) generation and function. Since the intestinal barrier dysfunction, together with the reduction in small intestine ILC3 and Treg numbers are associated with the pathogenesis of type 1 diabetes (T1D), the focus of this article is intestinal ILC3 modulation for the therapy of T1D. Of particular interest is free fatty acids receptor 2 (FFAR2), predominantly expressed on intestinal ILC3, that can be stimulated by available selective synthetic agonists. Thus, we propose that FFAR2-based interventions by boosting ILC3 beneficial functions may attenuate autoimmune response against pancreatic β cells during T1D. Also, it is our opinion that treatments based on ILC3 stimulation by functional foods can be used as prophylaxis in individuals that are genetically predisposed to develop T1D.